Musical learning, development and mediation: A case study of the Delta Langbroek Band in the Music van de Caab project in the Western Cape - Harper, Elizabeth (College of Music, 2017)
Musical learning, development and mediation: A case study of the Delta Langbroek Band in the Music van de Caab project in the Western Cape The Solms Delta wine estate's Music van de Caab project in the Groot Drakenstein Valley in the Western Cape has attracted a fair amount of informal attention nationally and internationally. Yet the methods and models of musical transmission and learning used in their music education remain unexplored territory in research. Gaining insight into community-based musical learning processes holds much value in music education, which has largely been dominated by formally taught Western music traditions and perspectives. This study aims to examine and describe the musical learning and facilitation processes of the Delta Langbroek Band, a brass band in the Music van de Caab project at Solms Delta wine estate, with regards to the modes and approaches to musical transmission. A theoretical framework, informed primarily by sociocultural perspectives on learning, uses Barbara Rogoff's design of three planes of analysis and the Twelve Continuum Transmission Framework proposed by Huib Schippers to investigate the musical learning system presented by the Langbroek band. Attention is also paid to oral and aural-based philosophies and teaching methods found on the African continent with specific reference to South Africa. Following a constructivist approach, the research is qualitative in nature with data collection through interviews and rehearsal observations of the Langbroek band of the Music van de Caab project over a period of seven months. Qualitative analysis using thick description and grounded theory is used to generate emergent patterns and themes from the data. Finally, findings from the literature review and data analysis are used in combination to contribute to a new emerging theoretical framework. Analysis of the learning and facilitation processes in the Langbroek band reveals a participation-based learning system with a combination of both aural and notation-based modes of musical transmission. Key findings from this study indicate that sites of informal and community music making serve as viable avenues and legitimate sites for musical development and learning. While making substantial use of theory, this study is grounded in empirical findings and could prove valuable for examining and refining curriculum content, as well as approaches to music instruction in formal music education South Africa. With a progressive awareness of the diverse models of musical learning and teaching around the world, further research at different sites of musical learning is extremely valuable.